Deep Learning and Implementastion in Islamic education - Yayan Supian; Rizaldy Alpiansyah; Irfan Alkhotiri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
This article examines the concept of deep learning as a contemporary pedagogical approach and critically relates it to the praxis of Islamic Education. Deep learning emphasizes conceptual understanding, critical reflection, learner engagement, and the construction of meaningful knowledge, rather than rote memorization or surface-level comprehension. In this framework, learning is understood as a transformative process that enables learners to internalize knowledge, connect ideas across contexts, and apply their understanding to real-life situations. Such an orientation aligns closely with the philosophical foundations of Islamic Education, which seeks to develop the human being holistically through the integration of intellectual, spiritual, moral, and social dimensions. Islamic Education is positioned in this article as a strategic and fertile domain for the implementation of deep learning, as its educational objectives inherently encompass cognitive, affective, and psychomotor development. The Islamic pedagogical tradition emphasizes processes of understanding (tafahhum), contemplation (tadabbur), and practice (‘amal ṣāliḥ), which resonate strongly with the principles of deep learning. Through reflective engagement with Qur’anic texts, Prophetic traditions, and socio-cultural realities, learners are encouraged to move beyond textual knowledge toward ethical awareness and responsible action. Employing a conceptual analysis supported by relevant educational and Islamic scholarship, this article argues that deep learning is highly compatible with the fundamental aims of Islamic Education. Specifically, it supports the formation of individuals who are not only intellectually competent, but also spiritually grounded and morally upright. Consequently, the integration of deep learning within Islamic Education offers a promising pedagogical pathway for cultivating meaningful learning experiences that contribute to personal transformation and social responsibility in contemporary Muslim societies.